Buku Saku Stimulasi Perkembangan Meningkatkan Pengetahuan dan Sikap Pada Ibu dI TK PEMBINA - Eko Suryani; Nurul Huda Syamsiatun (POLTEKKES KEMENKES YOGYAKARTA, 2016)
A child's growth and development is based on his age. The optimal growth and development depend on his biological potential. A child's biological potential is achieved by some factors which are interacted with one another such as genetic factor, bio-physical-psycho-social environment, and behavior. Stimulation hasthe important role to increase children's growth and development, especially to improve children's cognitive, afective, and psychomotor aspects. The ongoing stimulation causes good relationship among brain cells. Lack of stimulation will cause loss of function on brain cells and family role especially mother's role has a great deal in it. The aim of this study is to determine the effect of a pocket book entitled children growth stimulation at preschool age towards mothers' knowledge and attitude. There were 42 respondents. The measurement was conducted in 2 processes to get the data during the study. First, the respondents joined pre-test. Then, they were given pocket books. After 2 weeks, they got post test to measure mothers' knowledge and attitude. The data were analyzed by using paired t-test. There are effects on giving pocket book entitled children growth stimulation on preschool age towards mothers' knowledge, but it doesnot give any effect on the changes of mothers' attitude.